PENGARUH KOMPENSASI, MOTIVASI, DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN ATAU PEGAWAI DINAS PERTANIAN DAERAH ISTIMEWA YOGYAKARTA - Abdul Rohman; Utik Bidayati (Jurnal Fokus Manajemen Bisnis, 2015)
This study aims to determine whether compensation, motivation and job training affect the performance of employees or service employees Yogyakarta Special Region Agriculture and analyze the influential factors and has no effect on the performance of employees or employees of the Department of Agriculture Special Region of Yogyakarta. The sample in this study were employees or Dinas employees Yogyakarta Special Region of Agriculture. 84 samples were processed respondent. The sampling technique uses sampling purposive, the number of samples obtained was 84 respondents, i.e. sampling techniques with certain considerations. Considerations in this research is a permanent employee. Based on the results of statistical data analysis, the indicators of the study this is valid and the variables are reliable. Order individually from each of the most influential variables is the training variablework with a t test value of 3.758, then compensation with a t test value of 2,309. Then the variable that has no effect is the motivation variable with a t test value of -0.826. Yogyakarta Special Region Government needs maintain elements that have been assessed as good as giving Work compensation and training, and those with less influence need to be evaluated back to work motivation. The amount of influence caused (R2) by these three variables together to the bound of 0.229 or 22.9%, while the remaining 0.771 or 77.1% is influenced by other variables not examined in this study.